Srategi Rekrutmen dan Seleksi untuk Meningkatkan Kualitas Performance Kinerja di Sekolah Alam Pangandaran - Nunung Nurhasanah; Dicky Maryono (Lembaga Pengembangan Kinerja Dosen, 2025)
Sekolah Alam Pangandaran is committed to creating an inspiring and quality learning environment. One of the main keys in achieving this goal is through strategic recruitment and the right selection. In an effort to improve the quality of performance, the school implements a more holistic and inclusive approach, focusing on the values of nature and character education. The recruitment process not only considers academic qualifications, but also experience, passion, and suitability to the school's vision. The selection is carried out through a series of interviews, teaching simulations, and soft skills assessments, which allow time to recognize the potential and commitment of prospective educators. With this strategy, it is hoped that Sekolah Alam Pangandaran can present teaching staff who are not only competent, but also able to inspire and support the overall development of students. Recruitment and Selection Strategies to Improve the Quality of Performance in Natural Schools pangandaran. The researcher focused on how the recruitment and selection strategy was carried out at Sekolah Alam Pangandaran. The research method uses a type of qualitative descriptive research by collecting data through field research observations, interviews, field documentation, resource persons including 3 informants interviewed by the researcher, all from different sections. The results of this study illustrate that the recruitment and selection strategies carried out at Sekolah Alam Pangandaran are in accordance with the sequence of the selection process that must be carried out in schools.